Barriers to Access for Cervical and Breast Cancer Screenings Among Female Latinx Migrant Farmworkers in the US: A Scoping Literature Review - Ada Pariser; Kelly A. Hirko; Gladys M. Muñoz; Gladys Pico-Gleason; Chelsea Robinson; Jean M. Kerver (SAGE Publishing, 2022)
Identification of barriers to cancer screening among female migrant farmworkers is needed to inform intervention development and healthcare policy. Thus, our purpose was to systematically review and summarize findings from prior studies of barriers faced by Latinx migrant farmworkers in accessing cervical and breast cancer screenings in the US. Medline and Embase were used to identify literature through October 2021 using the search terms "migrant farmworkers AND. . .cancer; healthcare access; breast; cervical; federally qualified health centers," and "migrant cancer screening" and "migrant farmworker cancer screening." Snowball sampling by reviewing citations in each selected article was also used. Exclusion criteria included those articles that focused on specific types of cancer other than breast or cervical, those not within the US, not referencing Latinx migrants, not referencing cancer screening, or those focused on pediatric populations. Data was synthesized by 3 authors and selected articles were assessed for common themes. Nineteen articles met inclusion criteria. Common themes about barriers to cancer screening included: lack of cancer knowledge, cost/inability to pay, lack of health insurance coverage, cultural perceptions, fear, language difficulties, and transportation and time constraints. Findings suggest that barriers to cancer screening among migrant farmworkers may be addressed by providing education about cancer screening and treatment, addressing fear, language, and cultural barriers, and providing transportation and health insurance coverage. Consideration of these barriers is necessary to effectively address cancer disparities in this vulnerable population of female farmworkers.